White Diet with split‐dose Picosalax is preferred, better tolerated, and non‐inferior to day‐before clear fluids with polyethylene glycol plus sodium picosulfate‐magnesium citrate for morning colonoscopy: A randomized, non‐inferiority trial. Issue 1 (September 2017) - Dwyer, Jeremy P; Tan, Jonathan Y C; Paul, Eldho; Bunn, Catherine; Mangira, Dileep; Secomb, Robyn; Gibson, Peter R; Brown, Gregor
Abstract : Background and Aim: Bowel preparations with polyethylene glycol (PEG) and clear fluids are often poorly tolerated. We compared an innovative low‐residue White Diet and low‐volume, split‐dose Picosalax with the standard preparation at our institution of day‐before clear fluids and combination PEG plus sodium picosulfate/magnesium citrate (SPMC). Methods: Adults undergoing morning colonoscopy were randomized to either the White Diet and split‐dose, two sachets of Picosalax (WD/PICO) or day‐before clear fluids and 1‐L PEG plus two sachets of SPMC (CF/PEG + SPMC). The primary endpoint was successful bowel preparation defined by an Ottawa bowel preparation score ≤ 6. An intention‐to‐treat analysis with a predefined non‐inferiority margin of 15% was used to compare efficacy. Results: A total of 250 patients were randomized (125 WD/PICO and 125 CF/PEG + SPMC). WD/PICO was non‐inferior to CF/PEG + SPMC for successful bowel preparation by intention‐to‐treat analysis (58% WD/PICO vs 62% CF/PEG + SPMC, 95%CI: −14.2 to 6.2%) and per‐protocol analysis (64% WD/PICO vs 65% CF/PEG + SPMC, 95%CI: −11.3 to 9.4%). Patients in the WD/PICO group reported greater satisfaction with the diet ( P < 0.001), greater ease of following the diet ( P < 0.001), and improved experience compared with prior colonoscopy ( P < 0.0001), less bloating ( P = 0.02), less weakness ( P = 0.046), less hunger ( P < 0.0001), and less interference with daily activities ( P = 0.001). Procedure/withdrawal times and adenoma detection rates were similar between groups. Conclusion: Bowel preparation with the White Diet and low‐volume, split‐dose Picosalax was preferred and better tolerated without detriment to bowel preparation success compared with clear fluids and combination PEG plus SPMC for morning colonoscopy. Abstract : This prospective, single‐blinded, randomized, non‐inferiority trial showed that a low‐residue White Diet and low‐volume, split‐dose Picosalax is better tolerated, but with comparable bowel preparation quality to day‐before clear fluids and combination polyethylene glycol plus sodium picosulfate/magnesium citrate for morning colonoscopy.